Fibroblast Growth Factor-2 and the HIV-1 Tat Protein Synergize in Promoting Bcl-2 Expression and Preventing Endothelial Cell Apoptosis: Implications for the Pathogenesis of AIDS-Associated Kaposi's Sarcoma - Cecilia Sgadari; Giovanni Barillari; Clelia Palladino; Stefania Bellino; Brunella Taddeo; Elena Toschi; Barbara Ensoli (International Journal of Vascular Medicine)
Kaposi's sarcoma (KS) is a vascular tumor frequently occurring in Human Immunodeficiency Virus- (HIV-) 1-infected individuals. Our previous work indicated that the angiogenic fibroblast growth factor (FGF)-2 and the Tat protein of HIV-1, both expressed in KS lesions of HIV-infected patients, synergize at inducing angioproliferative, KS-like lesions in mice. Here we show that the development of angioproliferative lesions promoted in mice by combined Tat and FGF-2 associates with an increase in the levels of expression of the antiapoptotic Bcl-2 protein. Upregulation of Bcl-2 expression by combined FGF-2 and Tat occurs also in vitro, and this protects human primary endothelial cells from programmed cell death. As Bcl-2 is expressed in human KS lesions in a fashion paralleling the progression of the disease, these findings suggest a molecular mechanism by which Tat and FGF-2 cooperate in KS maintenance and progression in HIV-infected individuals.